Moral Dimensions of Artificial Intelligence: A Christian Ethical Perspective on its Impact on Education - Sugiri, Widjaja (Perkumpulan Teolog Agama Kristen Indonesia, 2024)
This article examines the integration of Artificial Intelligence (AI) in education through the lens of Christian ethics. With the rapid advancement of AI technologies, there is a growing need to explore how these innovations align with Christian values such as justice, human dignity, and compassion. The purpose of this study is to evaluate the moral dimensions of AI usage in educational settings and propose a framework for its ethical application. Using a qualitative research approach, the article conducts a literature review and case study analysis to understand how AI can be used responsibly in education. The findings suggest that AI has the potential to enhance personalized learning and accessibility but must be carefully designed and implemented to avoid biases, protect privacy, and support the holistic development of students in line with Christian teachings. Contribution: The article contributes to the ongoing discourse on AI ethics by offering a Christian perspective on its use in education. It provides a framework for evaluating AI applications in educational contexts, ensuring they align with moral principles that prioritize human dignity and justice. The study emphasizes the need for responsible implementation of AI to ensure it benefits all students equitably and ethically.